2021
DOI: 10.1108/ohi-11-2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of sense of belonging in the relationship between the built environment and victimisation: a case of Penang, Malaysia

Abstract: Purpose The current direction of urban planning and development is plagued with a number of issues related to crime and safety in neighbourhood areas. Undoubtedly, the physical characteristics of the surrounding environment play a vital role in residents’ social interactions and crime rate. This study aims to examine the role of the environmental features of the built environment, in particular house maintenance, on residents’ sense of belonging and victimisation. Although past research has relied on police vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Perception of safety refers to the degree to which individuals feel safe within their neighbourhood area [85,86]. Respondents were asked how safe they feel when (1) walking alone in the street during the day; (2) walking alone in the street after dark; (3) walking alone in neighbourhood during the day; (4) walking alone in neighbourhood after dark;…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Perception of safety refers to the degree to which individuals feel safe within their neighbourhood area [85,86]. Respondents were asked how safe they feel when (1) walking alone in the street during the day; (2) walking alone in the street after dark; (3) walking alone in neighbourhood during the day; (4) walking alone in neighbourhood after dark;…”
Section: Survey Instrumentmentioning
confidence: 99%
“…In another study, Ries et al ( 29 ) found that perceived plentifulness of facilities were connected with increased community physical-social activity such as neighborly interactions and communication. Abdullah et al ( 9 ) also identified that only perceived availability of parks and sports facilities had a significant influence on residential satisfaction rather than objective elements. It shows that perception could be an unignorable mediator between the objective built environment and SCB.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is argued that although increase in global mobility homogenizes sense of place, causing a loss of identity and traditional local community, people emotionally tend to search for local propinquity, belonging and identity (4,5). Thus, many scholars urge that policy makers, researchers and urban planners alike create the opportunities and conditions that facilitate and enhance SCB in living neighborhoods (9)(10)(11).…”
mentioning
confidence: 99%
“…First-generation CPTED emphasized that the physical built environment reduces crime rates [15]. Thus, first-generation CPTED focused on the designing of the built environment.…”
Section: Evolution Of Cptedmentioning
confidence: 99%